IMPLEMENTASI PMA NOMOR 30 TAHUN 2005 TENTANG WALI HAKIM - Sidiq, Muhammad Sirojudin (AS-SALAM, 2015)
A guardian is one of the foundations determining the marriage tobe either legal or illegal, hence however the situation, the guardianhas to be exist. If the parental guardians are not exist anymore, orunqualified to be a guardian, or mafqud, or not well-known addressed,or difficult to be called, so person who has a right to be a guardianin that marriage is magistrate guardian. Magistrate guardiansaccording to Islam are people who have authority in the country theylead the society. According to PMA No. 30 Year 2005 about MagistrateGuardian, there is explained that magistrate guardian is the Head ofsub-district KUA assigned by Ministry of Religion to be a guardian ofa bride who does not have any guardians. When the Head of KUA is onbusiness or not exist, the Head of Islamic Societal Guidance in act forthe Head of Ministry of Religion in District assigns one of the Headmenin Sub-district or closest place to be the magistrate guardian in hisplace temporarily.Keywords: According to PMA No. 30 Year 2005, Guardian of Marriage,Magistrate Guardian.